Green Chemistry Advances in Alternative Energy. - Benvenuto, Mark Anthony (Green chemical processing., 2022)
The continued greening of the energy sector, with inroads being made through numerous sources of materials that can produce energy, is the main focus of this, Green Chemical Processing, Volume 8. It includes contributions from area experts in widely different fields, all involved in energy production, and makes connections to the 12 Principles of Green Chemistry.